Confinement of nano-gold in 3D hierarchically structured gadolinium-doped ceria mesocrystal: synergistic effect of chemical composition and structural hierarchy in CO and propane oxidation. Issue 23 (25th October 2022) - Woźniak, Piotr; Małecka, Małgorzata A.; Kraszkiewicz, Piotr; Miśta, Włodzimierz; Bezkrovnyi, Oleksii; Chinchilla, Lidia; Trasobares, Susana
Abstract : Gadolinium-doped ceria hierarchical gold catalyst shows four-fold TOF increase compared to undoped non-hierarchical system, proving the synergistic effect of doping and structural hierarchy in propane oxidation. Abstract : Herein, the knowledge-driven design of multifunctional hierarchically structured gold on ceria catalysts for environmental applications is presented. Various configurations of gold-decorated ceria were obtained by a precise control of surface coverage parameters in the deposition–precipitation procedure. The activity of hierarchical catalysts in CO and propane oxidation was compared with that of the non-hierarchical gold-decorated nanocubes and nanoparticles. The synoptic description of the structural hierarchy and surface properties of materials investigated by various techniques (TEM, HRTEM, STEM-XED, SEM, ET, SI-EELS, ATR-FTIR, H2 -TPR, CO-TPR, TPD-MS, N2 physisorption, and NAP-XPS) has been presented to identify underlying phenomena controlling the catalytic activity and indicate the structure–activity relationships. Several merits of the material architecture such as the (1) surface area and porosity, (2) mutual arrangement of support crystallites, (3) nanoparticle confinement, (4) optimal size of nano-gold particles, and (5) increased metal–support contact were identified and discussed to explain the observed effect of the enhanced catalytic activity. Due to the extensive porosity induced by the structural hierarchy and nano-gold particles confinement, exceptional surface reducibility was observed, and the CO oxidation temperature shifted to the ambient regime ( T 50 = 18 °C) as compared to that of the gold-decorated nanocubes ( T 50 = 85 °C). In addition, the hierarchical catalysts showed substantial propane oxidation facilitation ( T 50 = 370 °C) as compared to that of the gold-decorated non-hierarchical catalysts ( T 50 = 480 °C). The synergistic effect of the structural hierarchy and support doping for propane oxidation enhancement is demonstrated. Moreover, the effect of the differences in the dopant-dependent catalyst architecture on the stability of gold nanoparticles is discussed. The knowledge of material architecture is necessary for the precise design of optimal multifunctional hierarchical catalysts.